Sexual side-effects of antidepressant and antipsychotic drugs. Issue 6 (November 2015) - Montejo, Angel L.; Montejo, Laura; Navarro-Cremades, Felipe
Abstract : Purpose of review: Psychotropic-related sexual dysfunction is a quite frequent issue in clinical practice, mainly in chronic treatments affecting both quality of life and compliance. Recent findings: In the last decade fortunately antidepressants and antipsychotic compounds have been deeply screened in order to identify sexual adverse events that were commonly underdiagnosed and previously underestimated by clinicians and perhaps by pharmaceutical companies as well. Some differences in the mechanism of action are the nucleus of this poorly tolerated adverse event. All antidepressants with serotonergic activity can cause mild to severe sexual dysfunction such as decreased libido and delayed orgasm frequently (>60%) or anorgasmia and arousal difficulties sometimes (30%). In contrast, noradrenergic, dopaminergic, or melatonergic antidepressants do not cause sexual dysfunction but perhaps the clinical profile of patients receiving these compounds could be different. Antipsychotics that highly increase prolactin levels and strongly block dopamine receptors could be related to sexual dysfunction as well. Unfortunately, these dysfunctions are present during the long term after the antipsychotic onset to provide continued symptom control and enable recovery. Young patients suffering psychosis and concomitant sexual dysfunction (erectile and/or orgasmic difficulties) tend to show poor compliance in chronic treatments affecting the outcomes. Summary: The implications of psychotropic-related sexual dysfunction in clinical practice are relevant mainly in patients under long-term treatment with previous satisfactory sexual life. Implications for future research about sexual dysfunction in all new treatments should be strongly taken into account.